Use of Henna (Lawsonia inermis) in the islamic perspectives / Neni Kartini Che Mohd Ramli, Noorshilawati Abdul Aziz and Rosita Aminullah - Che Mohd Ramli, Neni Kartini; Abdul Aziz, Noorshilawati; Aminullah, Rosita (2016)
Henna (Lawsonia inermis) is a flowering shrubs belongs to family Lythraceae is a medicinal plants that have many medicinal benefits and purposes to treats illness such as headache, mascular pains, skin disorders, hair treatment, rheumatism, jaundice and chicken pox. Futhermore, henna have been used widely in hand and nail decoratives and hair dye which close related to the wedding ceremony. In muslim culture, henna also being believed to has significant barakah where believed to carries good luck and fertility to the new bride and groom (it has barokah and protect against jnoun (jin). In Islamic perspectives, henna has never been mentioned anywhere in the Quran. However, henna usage is referred to several times in the Hadith. The plant is mentioned in the Hadith in twenty-two instances, out of which, eleven instances refer to men, five instances refer to the color of water of a contaminated well as being like 'an infusion of henna leaves', five instances refer to its use as body adornment and one instance refers to its use as medicinal treatments.